Dinamika Narapidana Dengan Gangguan Kepribadian Antisosial - Lembana Hawadini; Setyani Alfinuha (Jurnal Psikologi, 2023)
ABSTRACT An individual with antisocial personality disorder if meets the criteria in DSM V, such as a persistent pattern of violence, at least 18 years of age, conduct disorder, and the appearance of antisocial behavior without schizophrenia. Antisocial personality disorder is closely related to crimes committed by prisoners. This study aims to determine the psychological dynamics and personality disorders experienced by prisoners. In addition, the researchers also identified the factors that influence the disorder. This research is a qualitative research with a case study approach. The participants were one prisoner in Lapas X with cases of robbery and murder. This research is equipped with data from interviews, observations, and several psychological test tools to enrich the research results. The results showed that the conditions and experiences experienced by participants from childhood to adulthood influenced the formation of antisocial personality disorder. Furthermore, there are factors that influence the formation of the disorder, both internally and externally to the participants